2022
DOI: 10.1007/s00467-022-05781-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for neurocognitive impairment and the relation with structural brain abnormality in children and young adults with severe chronic kidney disease

Abstract: Background Severe chronic kidney disease (CKD) in children and young adults has shown to be associated with abnormal brain development, which may contribute to neurocognitive impairments. We aimed to investigate risk factors for neurocognitive impairment and investigate the relation with structural brain abnormalities in young severe CKD patients. Methods This cross-sectional study includes 28 patients with severe CKD (eGFR < 30), aged 8–30 years (media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that DTI parameters can detect the loss of white matter structural integrity in the brain (13)(14)(15)(16). However, our study contributes by highlighting that in patients with chronic kidney disease undergoing hemodialysis, if a routine brain MRI scan is normal, then there are no significant differences in DTI parameters compared with normal.…”
Section: Significant Differences In Dti Parameters In Ckd-mhd Populationmentioning
confidence: 68%
“…Previous studies have demonstrated that DTI parameters can detect the loss of white matter structural integrity in the brain (13)(14)(15)(16). However, our study contributes by highlighting that in patients with chronic kidney disease undergoing hemodialysis, if a routine brain MRI scan is normal, then there are no significant differences in DTI parameters compared with normal.…”
Section: Significant Differences In Dti Parameters In Ckd-mhd Populationmentioning
confidence: 68%
“…Slower processing speed has been associated with white matter and gray matter loss in some pediatric populations, such as preterm children [16,17]. White matter loss is also associated with chronic kidney diseases in both pediatric and adult populations [18,19]. Considering the typical onset of CAKUT during infancy, it is plausible that this condition exerts a more pronounced impact on the change of both white and gray matter compared to other etiologies of kidney failure.…”
Section: Discussionmentioning
confidence: 99%